2013
DOI: 10.5550/sgia.130902.se.006p
|View full text |Cite
|
Sign up to set email alerts
|

NIVO SPRINTERSKIH SPOSOBNOSTI, Eksplozivne snage I SPECIJALNE IZDRŽLJIVOSTI VRHUNSKIH MLADIH FUDBALERA NA RAZLIČITIM POZICIJAMA

Abstract: Cilj studije bio je da se analizira nivo sprinterske sposobnosti, eksplozivnih sposobnosti donjih ekstremiteta i specifične izdržljivost igrača u zavisnosti od pozicije u timu (golmani, odbrambeni igrači, vezni igrači, napadači) slovačkog fudbalskog nacionalnog tima ispod 21 godine (N=18, golmana n=2, odbrambenih igrača n=4, veznih igrača n=7, napadača n=5) tokom kvalifikacija za UEFA Evropskog prvenstva ispod 21 godinu 2011. Nivo sprinterskih sposobnosti dijagnostikovana je uređajem Fitro Light Gates (FiTRONI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 24 publications
1
3
0
Order By: Relevance
“…Assessment tests for explosive power of the lower extremities and the relative contribution of elastic potential (SJ, CMJ, and CMJA) showed no difference between team positions, which is in line with previous studies (Pivovarniĉek et al, 2013).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Assessment tests for explosive power of the lower extremities and the relative contribution of elastic potential (SJ, CMJ, and CMJA) showed no difference between team positions, which is in line with previous studies (Pivovarniĉek et al, 2013).…”
Section: Discussionsupporting
confidence: 92%
“…Most of the research has shown that explosive activities, like speed and agility do not differentiate players by playing position (Dauty, Bryand, & Potiron-Josse, 2002;Strudwick, Reilly, & Doran, 2002;Rampinini et al, 2007;Wisløff et al, 2004;Taskinen, 2008). There are several studies that have shown better results of forwards compared to other positions with regard to the sprint up to 20 m (Sporiš, Jukić, Ostojić, & Milanović, 2009;Pivovarniĉek, Pupiš, Tonhauserová, & Tokárová, 2013). On the other hand, in jumping activities, measured by squat jumps and countermovement jumps with an arm swing, significantly better results were observed in goalkeepers and central defenders (Lago-Penas, Lago-Ballesteros, & Rey, 2011; Boone, Vaeyens, Steyaert, Vanden Bossche, & Bourgois, 2012), while midfielders showed significantly lower scores than other positions on the team (Haugen et al, 2013).…”
Section: Introductionmentioning
confidence: 98%
“…However, it should be taken into account that the nature of agility movements is closely related to speed (Chaleh et al, 2012), which has been confirmed in many studies. Reilli et al (2000) state that football players do not have to have good motor skills, however, they must have an appropriately high level in all abilities (Pivovarniček et al, 2013). Research conducted by Nedeljković et al (2011) found that there are statistically significant differences between football players of the cadet age of FC Vojvodina and members of the Serbian national team in the 10 m run.…”
Section: Discussionmentioning
confidence: 99%
“…It is considered that a high level of motor skills is a basic prerequisite for efficient learning and performing new motor structures (Gardašević, et al, 2012). As some authors point out (Reilly et al, 2000;Pivovarniček et al, 2013), football players don't need to have exceptionally good motor skills, but they must have an appropriate level of all abilities. In accordance with the above, the aim of the research is to determine the differences in motor and functional abilities in football players of junior and cadet age.…”
Section: Introductionmentioning
confidence: 99%